Image and Effectiveness of Public Relations Media of Chiangmai Rajabhat University Towards the Decision of Admission for Mathayomsuksa 6 Students in Muang District Chiang Mai Province - sornsri, sirasa (Ganesha Journal, 2021)
This research aimed to study image, effectiveness of public relations media, and the relationship between effectiveness of public relations media and decision making to study in Chiang Mai Rajabhat University for Mathayomsuksa 6 students in Mueang District, Chiang Mai Province. The instrument consisted of questionnaires administered to 400 Mathayomsuksa 6 students. The descriptive statistics was for data analysis with the analyzed of single-component variance, tested the paired mean by the way of comparing multiple with the method of Scheffé. The study of image found that most of the respondents had opinions at a high level and the results of comparing the image by school pointed that different schools had different opinions on the image of Chiang Mai Rajabhat University with the statistically significant at 0.05 level. The results of the study of perception, exposure and liking public relations media revealed that most respondents were aware, exposed and liked public relations media from Rajabhat Chiang Mai University: facebook page. Finally, the study of the effectiveness of public relations media showed that the majority of respondents agreed that public relations media of Chiang Mai Rajabhat University had a high level of effectiveness, also, had an effect on the decision making for admission to Chiang Mai Rajabhat University with a high level of opinion.